(untitled) - ANDRIANI, SANTI (LATERNE, 2014)
Abstract Keywords: analytical, quantitative, validity, the product moment correlation The test is a set of tools or methods used to measure the degree of success or failure in achieving the objectives in teaching and learning activities. Test as a measure of student learning outcomes, are expected to provide information that can be accounted for truth. A test that can be said to be good as a gauge, if it has validity. This study was conducted with the aim of measuring the degree of validity of multiple choice questions Deuteronomy Increase Class (UKK) German language classes semester 4 XI Science SMAN 16 Surabaya. This research is a quantitative study because in the process of beginning to end is a lot of research is required to use numbers, ranging from data collection, interpretation of data, as well as the appearance of the result. The research method taken in this study is a statistical analysis. Statistical analysis in this study is to analyze the validity of using Product Moment Correlation formula. The results of this study indicate that the degree of validity of multiple choice questions Deuteronomy Increase Class (UKK) semester German language class XI Science SMAN 16 Surabaya fourth overall at 0:14 (low). And for testing the validity of an item about a 33% declared invalid by the number of items about 10 items of 30 items about. And about 67% declared invalid by the number of items about as many as 20 items of 30 items about. Problem that has high validity rate criteria are 3 point items about (10%). Log in sufficient validity criteria items about as much as 7 points (23%), while very low criteria entered in as many as 20 points about the items (67%). This study is expected to provide benefits and can be used as a guide for the further research, especially researchon the analysis of multiple-choice item-level validity.Auszug Schlüssel wort :analysieren, quantitative, validität, korelasi product moment Test ist ein Satz von Werkzeugen oder verwendet werden, um den Grad von Erfolgoder Misserfolg bei der Erreichung der Ziele im Lehr und Lernaktivitäten zumessen. Test als Maβ für die Schülerer warteten Lehrergebnisse, Informationen, die zur Gerechtigkeit gerechnet warden kann. Ein Test kann der gut zu sein wie Messgeräte, wenn ervalidität hat. Die Ziele dieser Untersuchung sind die validität der Multiple Choice Fragen von Deutschprüfung in der Erhöhung der zweiten Semester Klasse XI IPA 4 SMA Negeri 16 Surabaya zumessen. Die Untersuchung ist eine Quantitative Untersuchung, weil sie am Anfang bis zum Ende viel Zahlen gebrauchen, die von Datensammlung, Interpretation der Daten als auch das Aussehen des Ergebnisses. Die Untersuchungmethode in dieser Studie genommen ist eine Statistik Analyse. Statistik Analyse in dieser Studie ist für die Validität mit Korelasi Product Moment zu analysieren. Das Ergebnis der Untersuchung zegit, dass die Validität der Multiple Choice Fragen von Deutschprüfung in der Erhöhung der zweiten Semester Klasse XI IPA 4 SMA Negeri 16 Surabaya ingesamt sind 0.14 (niedrig). Und für die Prüfung der Validität ist 33 % als valid mit 10 Punkte von 30 Punkte. Und 67% als invalid mit 20 Punkte von 30 Punkte. Fragen mit dem höhe validität Kriterien gibt es 3 Punkte (10%). Die genug validität Kriterien gibt es 7 Punkte (23%), während die sehr gering validität Kriterien es 20 Punkte gibt (67%). Es wird gehöfft, dass die Untersuchung nützlich für die nächste Untersuchung. Durch ist die Untersuchung vor allem auf die Analyse des Validität der Multiple Choice Fragen von Deutschprüfung.